Peningkatan Kualitas Produk Tempe Melalui Penerapan Teknologi Terpadu Sistem Filter Air Di Desa Kolam Kecamatan Percut Sei Tuan - Herbert Sipahutar; Mukti Hamjah Harahap; Irham Ramadhani; Deo Demonta Panggabean; Dedy Husrizal Syah (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
The partners of this Community Partnership Program (PKM) are home-cooked tempeh entrepreneurs in the village of Pool, District of Percut Sei Tuan. Activities carried out as solutions to solve partner problems are 1) counseling on the impact of using unsuitable water for tempe production for health in the short and long term, 2) assistance in making integrated water filtration installations, 3) training and processing practices well water using integrated water filtration installations, 4. assistance in providing more hygienic production facilities. Based on the activities carried out, it can be concluded that: (1) Partners understand the negative impact on the health of using unclean water in producing tempeh. (2) Partners already have a water filter system installed at the tempe production site. (3) Partners already have the skills to use a water filter system to get clean water and how to treat it. (4) Partners have additional hygienic production equipment